Study on Green Decolorization Technology of Agar in the Extraction Process. (September 2020) - Cai, Ying; Wu, Zhanxia; Li, Sidong; Wang, Minting; Guo, Wanting; Hu, Zhang
Abstract: To establish a green decolorization technology of agar in the extraction process, the effects of activated carbon amount, decolorization time and decolorization temperature on the decolorization of agar solution extracted from Gracilaria rubra were investigated through single-factor tests with the decolorization ratio as an index. On the basis of single-factor tests, the decolorization process was optimized using orthogonal experiments. The results showed that the optimum conditions for decolorization with activated carbon were as follows: amount of activated carbon 0.6 g/100mL, decolorization time 5 min and decolorization temperature 70 °C. When the optimum conditions of decolorization with activated carbon were used on the basis of pre-treatment of diatomite, the decolorization rate of agar solution reached 81.6%, and the agar solution was nearly colourless, clear and transparent. The diatomite-pretreated decolorization of activated carbon overcame the disadvantages that chemicals are needed to acidify and bleach Gracilaria in the traditional agar extraction process. It not only avoided the use of chemicals, but also effectively decreased the water consumption and the amount of produced chemical-containing waste water.